Women and girls can transform food systems for climate resilience - Metcalfe, Jenni (CGIAR GENDER Impact Platform, 2022)
The article documented the COP27 side event organized by the CGIAR Gender Impact Platform and its partners to discuss three solutions for improving women’s access to climate resilience strategies.